1996
DOI: 10.21273/hortsci.31.7.1187
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Litchi Seed Germination

Abstract: Seed germination of four Litchi chinensis Sonn. cultivars (`Deshi', `Kasba', `Purbi', and `Early Bedana') was studied under various conditions, viz. in soil beds exposed to sunlight or in shade, in sand beds exposed to sunlight or in shade, and on moist filter paper. Among all, shaded, humid sand at 35 ± 2C gave the highest germination. Delaying sowing seeds after removal from the fruit significantly reduced germination. Litchi seeds held in polyethylene bags up to 4 days at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…Litchi seeds were seldom fully germinated when sown in a humid sand bed under shade or in carbonized rice hull (de Andrade et al, 2004;Prasad et al, 1996). We also observed that the traditional method of planting litchi seeds without any pretreatment resulted in inferior seedling uniformity and less efficiency in the production methods.…”
mentioning
confidence: 77%
“…Litchi seeds were seldom fully germinated when sown in a humid sand bed under shade or in carbonized rice hull (de Andrade et al, 2004;Prasad et al, 1996). We also observed that the traditional method of planting litchi seeds without any pretreatment resulted in inferior seedling uniformity and less efficiency in the production methods.…”
mentioning
confidence: 77%
“…Achieving the right balance and applying nitrogen (N), phosphorus (P), potassium (K) and sulfur (S) appropriately are crucial for enhancing both the physical and chemical characteristics of the soil in mustard farming. Effective nutrient management is crucial for maintaining soil quality and sustaining high crop production over time Prasad et al [8], Pal and Pathak, [9].…”
Section: Introductionmentioning
confidence: 99%
“…Seed treatment with Gibberellin increases the seed germination and seedling survival percentage (Ankaiah et al, 1993). Seed soaking in Ethephon and IBA enhances the germination (Prasad et al, 1996). In recent years, a few works were made on the promotion of germination in annual flower crops.…”
Section: Introductionmentioning
confidence: 99%